ANALISIS KORELASI PEARSON FAKTOR PENGARUH GENERATIVE AI TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA ITS SURABAYA - Darrel Athaya Refaldi; Achmad Faiz; Malvin Reynara Jawakory; Nur Aini Rakhmawati (Jurnal Sistem Informasi dan Aplikasi (JSIA), 2024)
This study aims to determine the effect of using Generative Artificial Intelligence (Gen-AI), specifically ChatGPT, on the critical thinking skills of students at the Sepuluh Nopember Institute of Technology (ITS) Surabaya. The research was conducted by distributing questionnaires to 53 ITS students containing questions about their perceptions of the ease of use, accuracy of answers, negative impacts on academics, and risks that may arise from the use of ChatGPT. The obtained data were then analyzed using Pearson correlation test and K-Means clustering. The results showed that there was no significant relationship between students' perceptions of the accuracy of ChatGPT's answers and its negative impact on academic activities. This means that students' perceptions of ChatGPT's accuracy do not affect their views on the potential negative impacts. K-Means clustering identified three groups of students with different perceptions of ChatGPT. Cluster 0 sees ChatGPT as a useful tool but remains wary of its potential negative impacts. Cluster 1 is unsure about the usefulness of ChatGPT. Cluster 2 is skeptical of ChatGPT's usefulness and more concerned about its negative impact on learning and originality of work. This research provides insight into how students view generative AI technology and can be a basis for further research on the impact of Gen-AI on education.